ผลของการจัดกิจกรรมบริการในห้องเรียนที่มีต่อจิตสาธารณะของเด็กปฐมวัย - ร้อยกรอง, ณัฐกานต์; ภิญโญอนันตพงษ์, สิริมา (วารสารวิจัยการพยาบาลและสุขภาพ, 2016)
การศึกษาวิจัยครั้งนี้มีจุดมุ่งหมายสำคัญเพื่อศึกษาและเปรียบเทียบระดับจิตสาธารณะของเด็กปฐมวัยก่อนและหลังการจัดกิจกรรมบริการในห้องเรียน กลุ่มตัวอย่างที่ใช้ในการศึกษาวิจัยครั้งนี้เป็นเด็กปฐมวัยชาย – หญิง อายุระหว่าง 5-6 ปี ที่กำลังศึกษาอยู่ระดับชั้นอนุบาล3 ภาคเรียนที่ 2 ปีการศึกษา 2557 โรงเรียนอิสลามสันติชน สังกัดสำนักงานคณะกรรมการส่งเสริมการศึกษาเอกชน จำนวน 15 คน ที่ได้รับการจัดกิจกรรมบริการในชั้นเรียนเป็นระยะเวลา 8 สัปดาห์ สัปดาห์ละ 3 วัน วันละ 30 นาที รวมทั้งสิ้น 24 ครั้ง เครื่องมือที่ใช้ในการศึกษาวิจัยครั้งนี้คือ แผนการจัดกิจกรรมการบริการในห้องเรียนและแบบประเมินพฤติกรรมจิตสาธารณะของเด็กปฐมวัย ซึ่งมีค่าดัชนีความสอดคล้องระหว่างพฤติกรรมกับจุดประสงค์ (IOC) อยู่ระหว่าง 0.67 – 1.00 และมีค่าความเชื่อมั่นเท่ากับ 0.64 การวิจัยครั้งนี้ใช้การทดลองแบบ One – Group Pretest – Posttest Designสถิติที่ใช้ในการวิเคราะห์ข้อมูลคือ t-test แบบ Dependent Sample และขนาดส่งผลของโคเฮน (Cohen’s d) ผลการศึกษาวิจัยพบว่า ระดับพฤติกรรมจิตสาธารณะของเด็กปฐมวัยรายด้านทุกด้านและโดยรวมก่อนได้รับการจัดกิจกรรมบริการในห้องเรียนอยู่ในระดับไม่แสดงพฤติกรรม หรือปฏิเสธ ( =0.54 ) หลังได้รับการจัดกิจกรรมการบริการในห้องเรียนอยู่ในระดับแสดงพฤติกรรมได้ด้วยตนเอง ( = 1.95 ) และผลการเปรียบเทียบพฤติกรรมจิตสาธารณะของเด็กปฐมวัยทุกด้านและโดยรวมมีการเปลี่ยนแปลงสูงขึ้นอย่างมีนัยสำคัญทางสถิติที่ระดับ .01 ด้านการดูแลรักษาของใช้ส่วนรวม (t=20.15**; d=5.20) ด้านการรับผิดชอบต่อส่วนรวม (t=16.14**; d=4.17) และด้าน การเคารพสิทธิในการใช้ของใช้ส่วนรวม (t=23.13** ; d=5.97) และโดยรวมทั้งหมด(t=36.47**; d=9.42) แสดงว่าการจัดกิจกรรมบริการในห้องเรียนส่งเสริมให้เด็กปฐมวัยมีคะแนนพฤติกรรมจิตสาธารณะรายด้านทุกด้านและโดยรวมมีการเปลี่ยนแปลงสูงขึ้นอย่างชัดเจนและขนาดส่งผลต่อพฤติกรรมจิตสาธารณะของเด็กปฐมวัยทุกด้านและโดยรวมอยู่ในระดับมาก The Effects of Services in Classroom Activity on the Public Mind of Preschool Children The purpose of this research was to study and compare the levels of public mind of preschool children before and after the use of services in classroom activity. The sample used in the study was 15 preschool boys and girls, with 5-6 years of age, who were studying in third year kindergarten in second semester of 2014 academic year at SantichonIslamic School under the Office of the Private Education Commission. The 24 experiments through the use of services in classroom activity were carried out within the period of 8 weeks, 3 days a week, and 30 minutes for each day. The research instruments were plans for services in classroom activity and an evaluation form for public mind of preschool children with the index of congruence (IOC) between behaviors and objectives between 0.67-1.00 and the reliability of.64.The research followed the one-group pretest-posttest design and the data were statistically analyzed by using dependent sample t-test and Cohen’s d effect size. The results of research revealed that, both in general and in all individual areas, the public mind behaviors of preschool children before the use of services in classroom activity were at the level of Not express behavior or deny(= 0.54) while the public mind behaviors after the use of services in classroom activity were at the level of Express behavior by themselves (= 1.95). Regarding the comparison of public mind behaviors of preschool children, both in general and in all individual areas, their behaviors were increasingly changed with statistical significance at the level .01 in the areas of Looking after the classroom things (t=20.15**; d=5.20), Being responsible for the classroom (t=16.14**; d=4.17), and Respecting rights when using the classroom things (t=23.13** ; d=5.97), and the total (t=36.47**; d=9.42). These results indicated that the services in classroom activity could obviously make the scores of public mind behaviors of preschool children higher, both in general and in all individual areas, and the effect sizes on the public mind behaviors, both in general and in all individual areas, were at the high level.